Effectiveness of Citrullus vulgaris rubrum and Solanum lycopersicum Juices on Reducing Blood Pressure in Hypertension Patients Aged 26-45 Years - Setianingsih, Nur Tias; Rachmawati, Kurnia; Nasution, Tina Handayani (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2023)
Hypertension is the second most common disease in the world, and the majority of those who suffer from it are adults. This study seeks interventions for lowering the prevalence of hypertension in the elderly and controlling blood pressure. This study compared the effects of tomato juice and watermelon juice in decreasing blood pressure in hypertensive patients at UPT Puskesmas Karang Intan 2 between the ages of 26 and 45, South Kalimantan. With pretest and post-test groups, this study used a quasi-experimental design. Thirty-two respondents were divided into intervention group 1 (watermelon juice) and intervention group 2 (tomato juice). Respondents were chosen based on research criteria and given interventions for five days. The Wilcoxon and Mann-Whitney tests were used to analyze the data. Watermelon juice and tomato juice had the same effect in lowering blood pressure in hypertensive patients aged 26 and 45 (p=0.102, =0.05). It implies that they were equally effective at lowering blood pressure because they contain the same beneficial substances in controlling blood pressure, such as potassium and citrulline.